UNDERSTANDING UNDERGRADUATES MONEY MANAGEMENT BEHAVIOR: A STUDY BEYOND FINANCIAL LITERACY - Armania Putri Wardhani; Muhammad Ubaidillah (PEOPLE: International Journal of Social Sciences, 2025)
Purpose: Undergraduate' money management behavior determines the smoothness of their transition into adulthood. Economic, social, and psychological factors also influence college students' money management behavior. Therefore, the purpose of this paper is to investigate how college students manage and respond to the economic, social, and psychological factors that influence their money management behavior, and to examine whether these responses change as they progress through their degrees.Methodology/approach: Qualitative Exploratory, Data were collected using six focus group discussions (FGDs), held at three universities in Indonesia, attended by 47 undergraduate students.Findings: The results showed that the way they handled their spending, income, savings, friendships, and stress changed as they moved through their studies. They both had similar ways of investing, followed their parents' money tips, and used technology to save money, no matter how far they were in their studies.Practical implications: The results of this study can help governments, banks, schools, and parents who want to teach college students good money management skills.Originality/value: This study goes beyond just talking about financial literacy. It has demonstrated how undergraduates' students react to different factors related to managing money and how these reactions change as they advance in their studies. This study used a qualitative exploratory method, instead of the usual quantitative methods that are often used for research on how undergraduates' students manage their money.